Time trends in maternal hypertensive disorder incidence in Brazil, Russian Federation, India, China, and South Africa (BRICS): an age-period-cohort analysis for the GBD 2021 - Xiaochan Wang; Fangqun Cheng; Qiupeng Fu; Peiyu Cheng; Jianzhong Zuo; Yuhang Wu (BMC, 2024)
Abstract Objectives Maternal hypertensive disorder (MHD) is a leading cause of significant maternal and fetal mortality and morbidity. The BRICS nations are crucial in the global MHD landscape, given their large populations and varied healthcare infrastructures. This investigation evaluates the incidence trends of MHD in BRICS countries from 1992 to 2021. Study design and methods Data on the number, all-age rate, age-standardized rate (ASR), and the relative change of MHD incidence from this study were sourced from the Global Burden of Disease (GBD) 2021 public dataset to investigate temporal trends in MHD incidence over three decades globally and in BRICS countries. The age-period-cohort (APC) model was used to estimate net drift, local drift, age-specific curves, and period (cohort) relative risks. Results A 15.87% increase in global MHD cases, alongside a 13.40% decrease in age-standardized incidence rates from 1992 to 2021. MHD incidence rates are declining across various BRICS age groups, except in China and Russian Federation, where most groups exhibit increasing trends. Annual net drift in MHD incidence ranges from − 4.25% in India to 2.38% in China. A shift in the age distribution of MHD cases from younger to older within the childbearing age range is observed in all BRICS nations. Countries exhibit similar age-effect patterns, with decreasing risk with increasing age, and varying period and cohort effects, indicative of differential control measures and temporal incidence trends. Conclusions Global and BRICS-specific reductions in MHD incidence vary in magnitude. Customized preventive strategies, leveraging existing resources, are advisable for BRICS nations to address pregnancy complications. Enhancing primary healthcare and maternal care quality, particularly for older mothers, is imperative.